INTERPRETATION OF THE QURAN VERSES ON MANAGEMENT OF FACILITIES AND INFRASTRUCTURE - Wati, Sartina; Ramadani, Teresia; Suwelda, Suwelda; Syahid, Abdul; Dakir, Dakir (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Abstract:This paper reveals the verses of the Qur'an that discuss the management of Islamic educational facilities and infrastructure. The verses are collected and then interpreted with several existing interpretations. This study uses a literature study method with a descriptive-analytical approach. The results of the study confirm that the management of educational facilities and infrastructure is a process that aims to manage and utilize all educational facilities and infrastructure effectively. The importance of this management of facilities and infrastructure is reinforced by views derived from the verses of the Qur'an. The purpose of the management of educational facilities and infrastructure is to ensure that educational institutions are able to provide professional services so that the learning process can take place effectively and efficiently. The implementation of educational facilities and infrastructure management includes planning, organizing, implementing and utilizing, inventorying, as well as supervision and maintenance.